2016
DOI: 10.4236/jssm.2016.95046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality Traits on Compulsive Buying Behavior: Mediating Role of Impulsive Buying

Abstract: The prime purpose of this study is to investigate the relationship between personality traits and compulsive buying behavior with mediating role of impulsive buying. By using quantitative research approach, convenience sampling method is selected. Data are collected by using previously established scales. Correlation coefficient and multiple regressions are applied to analyze directions and strength of relationship between variables. According to results agreeableness, neuroticism and openness to experience ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
(25 reference statements)
2
19
1
3
Order By: Relevance
“…Another finding to be mentioned is that impulsive consumption has a moderating effect between materialistic values and compulsive consumption (the sequence is MV--IC--CC). Compared with previous studies, impulsive consumption has impact on compulsive consumption (Kwak et al, 2006;Williams & Grisham, 2012;Shehzadi et al, 2016). This finding is also consistent with previous studies.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another finding to be mentioned is that impulsive consumption has a moderating effect between materialistic values and compulsive consumption (the sequence is MV--IC--CC). Compared with previous studies, impulsive consumption has impact on compulsive consumption (Kwak et al, 2006;Williams & Grisham, 2012;Shehzadi et al, 2016). This finding is also consistent with previous studies.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Another discussion in the literature whether impulsive and compulsive consumption behaviors were separate constructs (Kwak et al, 2006;Williams & Grisham, 2012;Williams & Grisham, 2012;Shehzadi et al, 2016). With this research, it was revealed that both impulsive and compulsive consumption behaviors are different constructs.…”
Section: Conclusion and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Individuals with high neuroticism demonstrate the tendency to show intense emotional responses (Brunault et al., 2018). Impulsivity can be regarded as a behavior that is more controlled by emotions rather than rationality (Peng, Feng, et al., 2019), so learning the predictive effect of neuroticism on impulsivity is not surprising (Chen et al., 2020; Shehzadi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This scale has been used in different contexts (e.g., in Argentina - Revilla et al, 2013;in Turkey -Shehzadi et al, 2016; in the United States - Sun et al, 2004;in Hong Kong -Thompson & Prendergast, 2015). The versions already translated to other languages have corroborated the instrument's one-factor structure and presented adequate indices of internal consistency (e.g., Revilla et al, 2013;Shehzadi et al, 2016). Considering the importance of this scale in the international context, it is believed that its use in Brazil would facilitate the exchange of information on the theme and comparisons between countries.…”
mentioning
confidence: 87%